Lightning activity associated with precipitation and CAPE over Bangladesh. (27th September 2017) - Dewan, Ashraf; Ongee, Emmanuel T.; Rafiuddin, M.; Rahman, Md. Masudur; Mahmood, Rezaul
ABSTRACT: Satellite‐derived lightning data for 17 years (1998–2014) were used to evaluate the relation between environmental factors and lightning activity over the Bangladesh landmass. Time series convective available potential energy (CAPE) data were extracted from ERA‐40 reanalysis data while total and convective rainfalls were obtained from Tropical Rainfall Measuring Mission's monthly products. In addition, the product of CAPE and precipitation was computed and used as an additional variable. Three timescales – monthly, seasonal and annual – were utilized to determine the influence of precipitation and CAPE on lightning activity. The results indicated that CAPE stands out as an important variable at all of these timescales for predicting the occurrence of lightning. The correlation coefficient ( r ) between CAPE and lightning activity was found to be 0.902 (monthly), 0.703 (pre‐monsoon), 0.550 (monsoon) and 0.702 (annual), respectively. Total rain showed strong positive correlation with lightning on monthly scale ( r = 0.734) and in the pre‐monsoon season ( r = 0.701). However, such relationship was moderate during monsoon ( r = 0.455). In contrast, convective rain showed slightly higher correlation during monsoon ( r = 0.587) compared with that of pre‐monsoon season ( r = 0.532). Because of strong seasonality in the data, convective rain did not exhibit strong relationship on annual scale ( r = 0.227). The product variable (e.g. CAPE × precipitation) showed significant correlation on monthly ( r = 0.895) and seasonal scales ( r = 0.818 during pre‐monsoon and 0.686 in monsoon) but its influence appears to diminish on a longer timescale ( r = 0.375). Spatial maps of correlation coefficient revealed significant positive correlation along relatively drier northern parts of Bangladesh. As lightning‐related fatality is on the rise, this study, first of its kind, is expected to inform public policy and provide information necessary for effective management of this atmospheric phenomenon to save lives and property in Bangladesh. Abstract : Lightning in Dhaka.